Railway track asset management modelling - Clarke, Steve (2021)
Railways are an important type of transport infrastructure but can be expensive to run with the UK railway costing £ 1.525~billion to maintain in 2018/19. To reduce the cost without reducing the quality of the infrastructure improved asset management is required. To enable the impact of possible decisions to be understood, and the optimum ones chosen, a railway track asset management model, such as the one developed in this thesis, is required.